Cash Transfers in Pandemic Times : Evidence, Practices, and Implications from the Largest Scale Up in History - Gentilini, Ugo (Washington, DC : World Bank, 2022)
Is Coronavirus (Covid-19) a “game changer” for cash transfers? This tantalizing question has animated a large body of recent literature and over 60 virtual panels. This paper offers some clues to address the question by bringing together data, evaluations and practical experiences generated over the course of the pandemic. In particular, the paper flashes out differences between Covid-19 and other crises; it lays out an anatomy of global responses and offers novel data analysis around stylized international trends; synthesizes fresh empirical evidence on response effectiveness based on over 40 evaluations; discusses country-level operational practices as emerging from an array of high and lower-income contexts; and distills key insights with possible future implications.